Pengaruh Corporate Social Responsibility, Kinerja Lingkungan dan Green Accounting Terhadap Kepemilikan Asing - Jasmine Fatimah Azzahra; Ai Hendrani (Masyarakat Ekonomi Syariah Bogor, 2025)
The phenomenon of environmental damage has become an important issue nowadays, for example like global warming, the greenhouse effect, and illegal logging are problems faced today. Foreign ownership themselves tend to care and pay attention to the surrounding environment where the company stands. The purpose of this study is to determine the influence of corporate social responsibility, environmental performance, and green accounting on foreign wnership in where companies is operating in basic and chemical industry listed on the IDX from 2019-2022. This study uses quantitative methods and data analysis using the SPSS program. Samples of this research is 10 companies multiplied by 4 years to 40 sample data. Result of partial test, the CSR variable has a positive effect on foreign ownership, the environmental performance variable has a positive effect but not significant on foreign ownership, while the green accounting variable proxied through environmental costs divided by net income shows a significant negative effect on foreign ownership. For further research, it can add profitability variables to see the comparison between variables related to the environment and the profits generated by the company.